EFEKTIFITAS PERENCANAAN PEMBANGUNAN DAERAH DENGAN PENDEKATAN PARTISIPASI MASYARAKAT DESA - IBRAHIM IBRAHIM; MULIATI MULIATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
Based on data from the Ministry of Villages, Development of Disadvantaged Regions and Transmigration, the number of villages in our country is 33,893 villages. This number of villages occupies more than 80% of the territory of the Republic of Indonesia. In an effort to realize the state's goal, namely to improve the welfare of the Indonesian people, the Government pays special attention to existing villages, especially in terms of implementing village development. With the spirit of